Production and characterisation of waste lignin and biodiesel-derived residues as potential bitumen modifiers - Weir Vargas, Ana I. (2022)
Most pavements around the world are built with asphalt comprising bituminous binders derived from fossil fuels. Bitumen traditionally fulfils the role of a binder in asphalt mixtures and provides tensile resistance and cohesion to the mixture. The binder’s rheological and adhesive properties allow these asphalt mixtures to withstand daily stresses such as traffic loads and environmental conditions without suffering excessive damage. Growing environmental concerns surrounding petroleum-derived bitumens have motivated the search for biobinders (binders manufactured from biomass) to be used in asphalt mixtures. In particular, waste biomass products are of interest due to their availability and impact on sustainability, but they generally need to be thermochemically treated before being used as biobinders. Biobinders have shown great potential to reduce bitumen demand and have exhibited good performance in terms of resisting common distresses affecting roads. However, detailed characterisation is still needed before they can be used in practice. The main objective of this project was to produce and characterise binders manufactured from waste biomass that can be used in pavements and encourage the development of sustainable and environmentally friendly solutions in pavement engineering. In this context, the focus of this project was to understand the chemical and rheological properties of waste lignin and biodiesel-derived residues in order to assess their suitability as potential biobinders. For this purpose, biobinders were produced via hydrothermal liquefaction and/or pyrolysis to obtain a higher viscosity bio-bitumen product. The research initially focused on the production and rheological characterisation of a lignin-containing paper waste residue via hydrothermal liquefaction (HTL). Although far too low yields of the paper waste biobinder were produced via HTL, these early results revealed that these biobinders are soft materials with lower stiffness compared to conventional bitumens. With further testing, a potential application for this material could be enhancing high-temperature performance due to an increased elastic response at these temperatures. Following this, the research centred on investigating the chemical and rheological properties of two biodiesel-derived residues before and after thermal treatment labelled Biofuel Oils (BFO). A comprehensive chemical characterisation was undertaken on the neat biomaterials before blending with bitumen in order to characterise the differences between the residues. This then led to the bio-modification of three penetration grade bitumens and the analysis of their rheological and ageing characteristics. The results showed that hydrothermal liquefaction is not an appropriate thermochemical treatment for the production of a higher viscosity biobinder from BFO materials due to the thermal decomposition of higher molecular weight compounds. However, the BFO can be upgraded to a higher viscosity product via thermal (pyrolytic) treatment to distil off lower molecular weight compounds. The rheological testing revealed that the addition of the BFO (original or pyrolysed) softens the bitumens by decreasing the complex modulus and increasing the viscous response. However, there is an increased stiffness and elastic response in the pyrolysed BFO compared to the starting materials. Although the biomodified bitumens showed the same ageing tendency as conventional materials, ageing occurred at a faster rate, which can be considered the main drawback of their performance. In light of the results obtained for the materials studied, the BFO can be considered a promising material in the improvement of low temperature cracking and fatigue performance due to the decrease in stiffness and increase in viscous response compared to aged or low penetration grade bitumens including recycled asphalt mixtures. With further research, a possible application for the higher viscosity pyrolysed BFO could be as an additive for warm mix asphalt pavements due its softer consistency than conventional materials. As a result, future work could focus on the implications of scale-up in the laboratory to produce higher quantities of the pyrolysed BFO for comprehensive asphalt mixture work.